MODIFIKASI FORMULA ENTERAL RUMAH SAKIT SIAP SEDUH - Suci Lestari; Meika Rahmawati A; Dewi Shita J; Listiyani Eka T (UNIVERSITAS NGUDI WALUYO, 2019)
Background:Kariadi Hospital utilizes a commercial formula for oral nutrition supplement (ONS) and enteral feeding. A commercial formula has been viewed as more superior compared to Blenderized Tube Feeding (BTF) due to its food safety and extended expiry date. However, a commercial formula may contribute to the higher cost. Developing powdered, hospital-made formula with low-cost and optimum food safety is essential. Objective:To develop powdered, ready to brewhospital-made formula and analyze the macronutrient content, microbiological, physical and organoleptic quality and total cost of the formula. Method:This study used univariate analysis with a descriptive design. Result:Macronutrient content in 1000 ml was 994,07 kcal of energy total, 37,2 g of protein, 26,8 g of fat, and 150,6 g of carbohydrate. The first Total Plate Count (TPC) test result was 0,9 x 102 CFU/ml and 1,1 x 102 CFU/ml for the second trial. There was no contamination of E.Coli dan Staphylococcus. The viscosity of the formula was 10,02 Cp, and the caloric density was 0,994 kcal/1ml. In organoleptic testing, most of the taste panels accepted the viscosity (80%), color (95%), odors (85%) and taste (75%). Food shelf life testing on day 4 and 11 were 0,4914 and 0,4914 (mg Malondialdehyde /kg sample). The cost of ready to brewhospital made formula was Rp. 39.586,80/1000 ml. Conclusion:Macronutrient composition, food microbiological, and physical quality of modified hospital-prepared enteral feeding was acceptable compared to the Indonesian standard. More than 80 % of the sensory panelist was satisfied based on the organoleptic test. Moreover, the cost was less expensive than commercial formula. Abstrak : Latar Belakang : Rumah Sakit dr Kariadi menggunakan formula komersial (FK) untuk oral nutrition supplement (ONS) dan enteral feeding. Penggunaan FK dipandang lebih superior dibanding formula rumah sakit (FRS) dari segi keamanan pangan serta masa kadaluwarsa yang lebih lama, namun penggunaan FK enteral lebih mahal dari FRS. Perlu adanya modifikasi FRS dengan keamanan pangan yang optimal dan biaya lebih terjangkau. Tujuan : Mengembangkan FRS bubuk siap seduh dan menganalisis kandungan zat gizi, mutu mikrobiologi, mutu fisik, mutu organoleptik dan biaya Metode : Penelitian univariat dengan desain penelitian deskriptif. Hasil ; Energi formula enteral dalam 1000 ml adalah 994,07 kkal, protein 37,2 gr, lemak 26,8 gr, dan karbohidrat 150,6 gr. Hasil uji Total Plate Count adalah 0,9 x 102 CFU/ml (Uji pertama) dan 1,1 x 102 CFU/ml (Uji kedua). Tidak ditemukan bakteri E.Coli dan Staphylococcus. Hasil uji viskositas adalah 10,02 Cp, densitas kalori sebesar 0,994 kkal dalam 1 ml formula. Hasil uji organoleptik menyatakan sebagian besar panelis suka terhadap kekentalan (80%), warna (95%), aroma (85%) dan rasa (75%) modifikasi FRS. Uji daya simpan dengan uji Thiobarbituric Acid diperoleh hasil MO 0,1014 dengan duplo 0,1716 (mg malonaldehid/kg sampel). Hasil M1 0,4914 dengan duplo 0,4914 (mg malonaldehid/kg sampel). Biaya FRS Rp. 39.586,80/1000 ml. Simpulan ; Kandungan gizi sesuai dengan komposisi umum untuk Indonesia, hasil uji mikrobiologi dan daya simpan dalam batas aman sesuai SNI, lebih dari 80 % sensory panelis menyukai FRS bubuk berdasar uji organoleptik. Biaya bahan lebih murah dibandingkan formula enteral komersial.